Son who returns - Robinson, Gary, 1950- (PathFinders (Summertown, Tenn.), 2014)
Fifteen-year-old Mark Centeno, of Chumash, Crow, Mexican and Filipino descent, goes to live with his grandmother on the Chumash reservation in California and learns traditional dancing in preparation for a dance competition at an upcoming powwow.